Morphology of media and communication companies in Ecuador [Morfología de los medios y empresas de comunicación del Ecuador] - Yaguache Quichimbo, J. (2012)
The paucity of information regarding the status of the communication companies in Ecuador, prompting the Department of Communication Sciences at the Technical University of Loja (UTPL) to develop a mapping of media, communication, production companies, advertising agencies and country s public relations. The need for a site consultation and reference on issues of communication, is still latent in Ecuador. While there are some contributions, both from private agencies as to build physical or virtual repositories, they have simply submit basic contact information and often outdated. With a sample of over 1000 media access know its form and substance, itself, distributed morphology and corporate legal organization, location, content, scope, and services provided. It is an informative approach to reality in the country and is part of the macro research called Map of Ecuador communication .